Factors Affecting Business Angels Investment in Vietnam - Nguyen Thi Kim Anh; Vu Thanh Huong; Nguyen Thi Minh Phuong; Dang Thanh Dat (Ital Publication, 2023)
The paper aims at investigating and comparing the factors determining investment decisions by business angels (BAs) from the viewpoints of BAs and startups in Vietnam based on a framework synthesized from a literature review and primary data from in-depth interviews conducted with 8 startups and 15 angel investors. The results show that the startups’ founder, working team, financial issues, product and market, and strategy related to exit and the roles of BAs are startup-related factors determining BAs’ investment in Vietnam. For BA-related factors, the BAs’ experience, investment objectives and preferences, and culture are key determinants. The novelty of the paper is to find out the gaps between the perspectives of BAs and startups, and the difference between Vietnamese and foreign BAs’ viewpoints. The finding is that BAs, more strictly than startups, assess their business plan, financial state, product, market, and targeted consumers. Startups neglect the exit strategy and role of BAs in invested startups. In addition, foreign and domestic BAs have different opinions on startups’ market scale, and expectation of profits and BAs’ roles in startups. The paper ends by providing some implications for Vietnamese startups to attract more angel investment, focusing on improving the quality of human resources, developing a profitable, honest, and realistic business plan, and setting up a long-run vision towards the global market. Doi: 10.28991/ESJ-2023-07-02-07 Full Text: PDF